Comprehensive MicroRNAome Analysis of the Relationship Between Alzheimer Disease and Cancer in PSEN Double-Knockout Mice - Ham, Suji; Kim, Tae Kyoo; Ryu, Jeewon; Kim, Yong Sik; Tang, Ya-Ping; Im, Heh-In (KOREAN CONTINENCE SOC, 2018)
Purpose: Presenilins are functionally important components of gamma-secretase, which cleaves a number of transmembrane proteins. Manipulations of PSEN1 and PSEN2 have been separately studied in Alzheimer disease (AD) and cancer because both involve substrates of gamma-secretase. However, numerous clinical studies have reported an inverse correlation between AD and cancer. Interestingly, AD is a neurodegenerative disorder, whereas cancer is characterized by the proliferation of malignant cells. However, this inverse correlation in the PSEN double-knockout (PSEN dKO) mouse model of AD has been not elucidated, although doing so would shed light onto the relationship between AD and cancer. Methods: To investigate the inverse relationship of AD and cancer under conditions of PSEN loss, we used the hippocampus of 7-month-old and 18-month-old PSEN dKO mice for a microRNA (miRNA) microarray analysis, and explored the tumor-suppressive or oncogenic role of differentially-expressed miRNAs. Results: The total number of miRNAs that showed changes in expression level was greater at 18 months of age than at 7 months. Most of the putative target genes of the differentially-expressed miRNAs involved Cancer pathways. Conclusions: Based on literature reviews, many of the miRNAs involved in Cancer pathways were found to be known tumor-suppressive miRNAs, and their target genes were known or putative oncogenes. In conclusion, the expression levels of known tumor-suppressive miRNAs increased at 7 and 18 months, in the PSEN dKO mouse model of AD, supporting the negative correlation between AD and cancer.
Keywords: GAMMA-SECRETASE; PRESENILIN 2; SYNAPTIC PLASTICITY; TUMOR-SUPPRESSOR; INHIBITION; MECHANISM